1990
DOI: 10.1136/bjo.74.5.311
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma metastatic to the contralateral orbit

Abstract: In a 9-month-old girl a subperiosteal metastasis of the maxillary bone developed in the contralateral orbit about one year after enucleation of a poorly differentiated retinoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The distant bones most commonly affected by retinoblastoma metastasis are the ribs and vertebrae, which are the most active in the haematopoietic system, especially in children [ 13 ]. Retinoblastoma metastasis to the contralateral orbit, maxilla and mandible has been reported in previous articles [ 14 , 15 ]. Metastasis to the soft tissue is very rare.…”
Section: Discussionmentioning
confidence: 98%
“…The distant bones most commonly affected by retinoblastoma metastasis are the ribs and vertebrae, which are the most active in the haematopoietic system, especially in children [ 13 ]. Retinoblastoma metastasis to the contralateral orbit, maxilla and mandible has been reported in previous articles [ 14 , 15 ]. Metastasis to the soft tissue is very rare.…”
Section: Discussionmentioning
confidence: 98%
“…However, the finding of three cases of contralateral orbital recurrence in our series suggests that non-contiguous tumour spread may be an under-recognised mechanism for orbital relapse in some of these cases. Haematogenous metastasis to the ipsilateral or contralateral orbit has been reported as a mechanism for orbital recurrence, particularly to the orbital bones28 29…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the majority of occurrences of ocular tumor spread to the contralateral eye are malignant melanoma, with infrequent reports of retinoblastoma and lymphoma ( 22 , 23 ). Bilateral primary tumors of different types are very uncommon, and our pathologic findings confirmed that both were MECs.…”
Section: Discussionmentioning
confidence: 99%